(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2025)
This paper explores the Taxation system in the Republic of Kosovo. It researches the need and reasons for the optimal taxation system that the Republic of Kosovo should develop as part of the proposed Taxation reform (based on recommendation). The Republic of Kosovo is the newest country in Europe. Since 2000, one of its core pillars has been the Tax Administration, which serves as the primary public finance income generator. Its further development, reform, and adaptation with updated Taxation mainstreams is imperative. Taxation systems should implement the best practices in digitalization and innovation. The paper uses secondary data with analyzed findings based on the quantitative empirical approach. The findings show that there is room for the Republic of Kosovo to apply Taxation reforms to further enrich, innovate, and upgrade its Tax system. As stated, the country’s economic and business development significantly depends on how its taxation system meets its development and strategic goals. This research paper concludes with concrete recommendations that the Republic of Kosovo is advised to undertake in reforming its Taxation system.